(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
In the living world, 1.5 billion of people have been suffering from either one or another brain disease. The most probably causing diseases/disorders related to the function of the brain were autoimmune encephalitis, autoimmune epilepsy, Hashimoto’s encephalopathy, Alzheimer’s disease (AD), and Wilson’s disease. As the brain’s extracellular matrix contributes to the poorly distributed delivery of locally administered medications and the blood-brain barrier functions as an impenetrable barrier for systemically injected treatments, drug targeting in the brain is one of the most difficult problems in pharmaceutical research. General strategies that can enhance medication delivery to the brain are very desirable for the treatment of several disorders affecting the central nervous system (CNS). When medications are given close to their optimal sites of action, they are both less hazardous and more effective. Several methods or novel approaches have been developed through various investigations to target the drug to reach the affected area in the brain. The BBB is the most hurdles for the active ingredients to exhibit its function so numerous approaches such as Nanoparticles, Lipoplexes, Scaffolds, Dendrimers, Polyanhydride, and Receptor-mediated transport (RMT) have been developed for improving drug action.